PAJAK PERUSAHAAN DAN EXCHANGE RATE TERHADAP TRANSFER PRICING PADA PERUSAHAAN KIMIA - Dini Martinda Lestari; Ela Yulia Dewi; Surachman (Valuasi : Jurnal Ilmiah Ilmu Manajemen dan Kewirausahaan, 2021)
Transfer pricing is carried out by multinational companies specifically between related parties. The purpose of this study is to study the effect of corporate tax and exchange rates on transfer prices. This research was conducted at chemical industry sub sector manufacturing companies listed on the Indonesian Stock Exchange (IDX) using purposive sampling method. Samples were obtained by 10 companies with a 3-years observation period, so that the final sample was obtained by 30 companies. Data is obtained by collecting annual financial reports (annual reports) of sample companies obtained on the Indonesian Stock Exchange for the period of 2016-2018. The analysis technique used in this study is multiple linear regression. The results of this study prove that corporate tax and exchange rates have an influence on transfer prices. The coefficient of determination of 0.239 shows that 23.9% of the variable transfer price can be determined by the independent variables. While resolved by other reasons.